A portfolio perspective on euro area bank profitability using stress test data - Harun Mirza; Carmelo Salleo; Zoe Trachana (European Central Bank (ECB), 2024)
This study assesses euro area banks' profitability using granular stress test data from three EU-wide exercises, coordinated by the European Banking Authority, that took place in 2016, 2018, and 2021. We propose a credit portfolio-level risk-adjusted return on assets for the euro area as a whole and for individual countries to assess the profitability of lending activities among euro area banks. Using banks' own projections under the adverse scenarios of the stress test exercises for a consistent sample of euro area banks, we aim to uncover the effect of severe macroeconomic and financial conditions on the profitability of the various portfolios. We investigate how many country portfolios switch from profitable to loss-making under adverse conditions and show that this number peaks in the 2018 stress test exercise, while the 2021 exercise yields the lowest overall profitability. Overall, around 30% of exposures become unprofitable under stress conditions across the latest two exercises (compared to 20% for the 2016 exercise), mostly concentrated in the nonfinancial corporations (NFC) segment and, to a lesser extent, in the financial and mortgage portfolios. We also show in a regression analysis that the yield curve is an important determinant of portfolio-level profitability in a stress test setting, while the unemployment rate seems to be relevant in determining portfolio switches and GDP growth seems to influence the change in profitability. The results also point to some portfolio heterogeneity.
Keywords: G01; G17; G21; 330; Bank profitability; net interest income; cost of risk; stress testing; scenario analysis; portfolio analysis